Development of Syntax Acquisition in 3-Year-Old Children: A Longitudinal Study - Siti Ismahani; Lutfi Putri Khairani; Sonia Sabilla; Tiara Putri; Yusriani (VISA: Journal of Vision and Ideas, 2024)
A longitudinal study of syntax acquisition in three-year-old children provides a deeper understanding of how children develop their language abilities. By summarizing the findings from this research, we hope to take concrete steps to support optimal language development in the early stages of a child's life. This research uses the literature review research method, the literature review research method is an approach that involves examining and analyzing existing literature or research to gain a thorough understanding of a topic or research question. This process begins by determining the research topic and searching for relevant literature through various sources such as academic databases and digital libraries. The findings of this research provide a strong basis for designing early childhood education programs that pay attention to syntax acquisition patterns. Learning materials can be arranged according to children's developmental stages to support their optimal development. In addition, this research confirms that understanding language development at an early age can act as an indicator of children's psychological health. Monitoring syntax acquisition can help detect potential developmental problems or disorders early, opening up opportunities for more effective intervention.